Development of a Meibomian Gland Dysfunction–Specific Symptom Questionnaire. Issue 1 (January 2018) - Paugh, Jerry R.; Kwan, Justin; Christensen, Michael; Nguyen, Andrew Loc; Senchyna, Michelle; Meadows, David
Abstract : Objectives: The aim of this study was to develop and evaluate, using psychometric approaches, a meibomian gland dysfunction (MGD)-specific questionnaire in noncontact lens wearers. Methods: The MGD subjects were recruited and classified as the MGD dry eye subtype based on accepted tests (e.g., Schein symptom survey, tear breakup time, corneal and conjunctival staining, abnormal meibum or meibomian gland atrophy, and a normal Schirmer test). The MGD questionnaire items were drawn from published and anecdotal sources. The preliminary instrument contained 24 items targeting the frequency and intensity of 12 symptoms. Rasch analysis was used for psychometric evaluation of the survey items. Results: Sixty nine MGD subjects completed the survey and clinical testing. Sample severity levels were as follows: none subclinical, 10 minimal, 43 mild, 16 moderate, and none severe. Three iterations of analysis, eliminating INFIT and OUTFIT scores <, and >3.0, and using subject responses reduced the final questionnaire to seven question pairs. Final analysis for the remaining 14 items demonstrated an excellent fit to the Rasch model (e.g., for persons, INFIT MNSQ=0.97; ZSTD=−0.2; OUTFIT MNSQ=0.96; ZSTD=−0.2; item fit statistics were similar). Construct validity also seems good (e.g., correlation to Schein and change with treatment). Conclusions: The MGD-specific instrument is a valid quantitative measure of the symptoms stemming from MGD sufferers. Further research is necessary to determine whether diagnostic efficacy is sufficient to differentiate the MGD dry eye subtype in an independent sample of normals and both major dry eye subtypes exhibiting a broad severity range. Abstract : Supplemental Digital Content is Available in the Text.